Implementation Role of HR in Organizational Transformation as Agent of Change - Shinta Ratnawati; Hanung Eka Atmaja; Budi Hartono (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2021)
An organizational transformation that results in